(3CQHYhf MOjkKG hTQMgGs - (3eMeO Hf CHj HcQs ((3GdMGL YHOGdQShd GHf edGMf GdeTghQ HeLGQ ecg GdecQeI s)
(3ChdgG (B:s
(3hHYO aEf GdYHO GdePfH eMeO Hf CHj HcQ QMeI Gddg Ydjg HYO Whd NhVg aj HMQ GdPfhH hGdYUjGf WdH QVG GdQMef heNGdaI ddTjWGf aLeY GdYHO CQHYjf MOjK HGdCSGfjO GdoeJUdI Edi GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3bGd GdQShd Udi Gddg Ydjg hSde SdehG Ydi GdjghO hdGoJSdehG Ydi jghOj CeJj abGd Ydj cQe Gddg hLgg hQVi Gddg Yfg(B: (3jGQShd Gddg heG jghO CeJc abGd(B: (3ef SeY GdCPGf hGdEbGeI hde jMVQ GdLeGYI agh jghO CeJi UOb QShd Gddg Udi Gddg hUOb MHjH Gddg JeJ hHs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI SYjO GdOjhg Li (B- (3GdehUd (B(2/125) s
Keywords: (3GdMOjK h GdeUWdMs